The Analysis of The Translation of 'אֲמֻצִּים' In Zechariah 63 and 67 - Philip Suciadi Chia (Theological Journal Kerugma, 2018)
There are some ancient sacred texts for Christianity such as Hebrew Bible, Syriac Peshitta, Septuagint, Aramaic Targum and Latin Vulgate. However, the translation of these ancient texts is not always having the same nuance or literal meaning. Zechariah 6:3 and 6:7 are one example. The word “אֲמֻצִּים” or strong has been translated diversely in our ancient sacred texts. Therefore, this paper will attempt to discuss multiple translations for the word “אֲמֻצִּים” or strong. The discussion will cover the purpose of these various translations. The possible reason behind the selection of the meaning will also be discussed in this paper.